Purification and Molecular Genetic Characterization of ZPU1, a Pullulanase-Type Starch-Debranching Enzyme from Maize - Beatty, Mary K. (American Society of Plant Physiologists, 1999)
This study identified and purified specific isoamylase- and pullulanase-type starch-debranching enzymes (DBEs) present in developing maize (Zea mays L.) endosperm. The cDNA clone Zpu1 was isolated based on its homology with a rice (Oryza sativa L.) cDNA coding for a pullulanase-type DBE. Comparison of the protein product, ZPU1, with 18 other DBEs identified motifs common to both isoamylase- and pullulanase-type enzymes, as well as class-specific sequence blocks. Hybridization of Zpu1 to genomic DNA defined a single-copy gene, zpu1, located on chromosome 2. Zpu1 mRNA was abundant in endosperm throughout starch biosynthesis, but was not detected in the leaf or the root. Anti-ZPU1 antiserum specifically recognized the approximately 100-kD ZPU1 protein in developing endosperm, but not in leaves. Pullulanase- and isoamylase-type DBEs were purified from extracts of developing maize kernels. The pullulanase-type activity was identified as ZPU1 and the isoamylase-type activity as SU1. Mutations of the sugary1 (su1) gene are known to cause deficiencies of SU1 isoamylase and a pullulanase-type DBE. ZPU1 activity, protein level, and electrophoretic mobility were altered in su1-mutant kernels, indicating that it is the affected pullulanase-type DBE. The Zpu1 transcript levels were equivalent in nonmutant and su1-mutant kernels, suggesting that coordinated regulation of ZPU1 and SU1 occurs posttranscriptionally.